Modular minimally invasive extracorporeal circulation ensures perfusion safety and technical feasibility in cardiac surgery; a systematic review of the literature. (November 2022) - Anastasiadis, Kyriakos; Antonitsis, Polychronis; Asteriou, Christos; Deliopoulos, Apostolos; Argiriadou, Helena
Introduction: Despite extensive evidence that shows clinical of superiority of MiECC, worldwide penetration remains low due to concerns regarding air handling and volume management in the context of a closed system. The purpose of this study is to thoroughly investigate perfusion safety and technical feasibility of performing all cardiac surgical procedures with modular (hybrid) MiECC, as experienced from the perfusionist's perspective. Methods: We retrospectively reviewed perfusion charts of consecutive adult patients undergoing all types of elective, urgent, and emergency cardiac surgery under modular MiECC. The primary outcome measure was perfusion safety and technical feasibility, as evidenced in the need for conversion from a closed to an open circuit. A systematic review of the literature was conducted aiming to ultimately clarify whether there are any safety issues regarding MiECC technology. Results: We challenged modular MiECC use in a series of 403 consecutive patients of whom a significant proportion (111/403; 28%) underwent complex surgery including reoperations (4%), emergency repair of acute type A aortic dissection and composite aortic surgery (1.7%). Technical success rate was 100%. Conversion to an open circuit was required in 18/396 patients (4.5%), excluding procedures performed under circulatory arrest. Open configuration accounted for 40% ± 21% of total procedural perfusion time and was related to significant hemodilution and increase in peak lactate levels. Systematic review revealed that safety of the procedure challenged originated from a single report, while no clinical adverse event related to MiECC was identified. Conclusions: Use of modular MiECC secures safety and ensures technical feasibility in all cardiac surgical procedures. It represents a type III active closed system, while its stand-by component is reserved for a small (<5%) proportion of procedures and for a partial procedural time. Thus, it eliminates any safety concern regarding air handling and volume management, while it overcomes any unexpected intraoperative scenario.